Prognostic Value of the Lymphocyte‐to‐Monocyte Ratio in Patients with Parotid Gland Carcinoma. (16th July 2020) - Mikoshiba, Takuya; Ozawa, Hiroyuki; Watanabe, Yoshihiro; Sekimizu, Mariko; Saito, Shin; Yoshihama, Keisuke; Nakamura, Shintaro; Imanishi, Yorihisa; Kameyama, Kaori; Ogawa, Kaoru
Abstract : Objective: Previous studies have evaluated various markers as prognostic predictors in patients with many types of cancers. However, the influence of such factors on the outcomes of patients with parotid gland carcinoma (PGC) is unknown. This study investigated the roles of alternative markers in the prognoses of patients with PGC. Methods: Overall, 101 patients who underwent curative treatment for PGC were retrospectively evaluated, and their 5‐year overall and disease‐free survival rates were calculated. The prognostic values of clinical and pathologic factors were determined. Results: The 5‐year overall and disease‐free survival rates were 73.1% and 62.8%, respectively. Multivariate analysis revealed that a low lymphocyte‐to‐monocyte ratio (LMR), high T classification, high N classification, and perineural invasion were independent predictors of poor prognosis. Conclusions: Thus, we identified LMR as an independent prognostic factor for patients with PGC. Patients with low LMRs who are amenable to treatment may require adjuvant treatment to improve their prognoses. Level of Evidence: 4 Laryngoscope, 131:E864–E869, 2021